Recent advances in postharvest technologies for reducing chilling injury symptoms of fruits and vegetables: A review - Jiaxin Wu; Rui Tang; Kai Fan (Food Chemistry: X, 2024)
Low temperature storage is widely used in the storage and transportation of postharvest fruits and vegetables. However, the negative effects of chilling injury (CI) on certain fruits and vegetables cannot be ignored. Therefore, efficient CI prevention technologies were used for reducing CI. This paper expounds the mechanisms of CI, common symptoms of CI and its impacts on the quality of fruits and vegetables, and summarizes the application of CI prevention technology. CI control methods are mainly classified into physical treatments (hot shock, near-freezing storage, high relative humidity storage, light-proof storage, and electromagnetic field), chemical treatments (melatonin, 1-methylcyclopropene, astragalus polysaccharides, γ-aminobutyric acid, 24-epibrassinolide, methyl jasmonate, trisodium phosphate, glycine betaine, and salicylic acid, etc.), coating treatments (sodium alginate, chitosan, carboxymethyl cellulose and aloe vera gel, etc.) and their combined treatments. These treatments have enhanced antioxidant activity, enzyme activity, membrane system integrity, and energy levels, thereby reducing the CI of fruits and vegetables.